Clinical Vignettes: Integrated Care of Cancer Patients by Oncologists and Cardiologists - Hofstatter, Erin; Saadati, Hamid; Russell, Kerry; Russell, Raymond (Current Cardiology Reviews, 2011)
Because of the paucity of large, randomized trials concerning the cardiac care of patients with cancer, treatment and prevention of chemotherapy-induced cardiotoxicity must rely on insights gained from small trials and case reports as well as the application of guidelines developed for the general population. In these clinical vignettes, we present patients referred by their oncologists to a cardiologist for specialized evaluation and management of cardiotoxicity with the goal of emphasizing the importance of identifying risk factors for cardiotoxicity, initiating evidence-based therapy, and establishing a close collaboration between oncologists and cardiologists.
Keywords: cancer recurrence